Literary theory : the basics - Bertens, Johannes Willem (New York : Routledge, 2001)
An introduction to literary theory that provides information on the major approaches to literature and the historical contexts of each critical movement, covering topics such as Marxism, feminism, structuralism, deconstruction, and new historicism.
Includes bibliographical references (p. 237-246) and index.
Adult.
Adult
Keywords: Criticism -- History -- 20th century; Literature -- History and criticism -- Theory, etc; Criticism -- History; Literature -- History and criticism